Gizi Ibu: Fondasi Menyusui dan Masa Depan Anak: Maternal Nutrition: The Foundation of Breastfeeding and Beyond - Basrowi, Ray Wagiu; Darus, Febriansyah; Sundjaya, Tonny; Arumndari, Runi (Universitas Airlangga, 2025)
Background: Breastmilk from a healthy and well-nourished mother serves as the optimal source of nutrition for infant growth and development. The composition of breastmilk is affected by maternal dietary patterns. Beyond its nutritional value, breastfeeding fosters emotional bonding between the mother and infant. Objectives: This study aims to explore the role of maternal nutrition in breastfeeding success and infant’s well-being through scientific and philosophical lenses. Methods: Literature search was conducted via PubMed (Medline Database), including systematic reviews, meta-analyses, and original research articles published within the last decade (2014-2024). The following keywords were utilised: (